Analysis of the maternal inheritance hypothesis of the exochorium in eggs from hybrids of Chagas disease vectors - de Sousa, Paulo Sergio [UNESP]; de Oliveira, Jader; Ravazi, Amanda [UNESP]; dos Reis, Yago Visinho [UNESP]; de Azeredo Oliveira, Maria Tercília Vilela [UNESP]; da Rosa, João Aristeu [UNESP]; Galvão, Cleber; Alevi, Kaio Cesar Chaboli (Springer Nature, 2024)
Morphological studies applied to the taxonomy of the Triatominae cover various structures (head, wing, thorax, genitalia, and eggs). Exochorial structures of hybrid eggs were characterized and compared with the parents, demonstrating that hybrids presented characteristics identical to the exochorial pattern observed in the females of the crosses, which resulted in the hypothesis that the pattern of triatomine eggs is possibly a characteristic inherited from females. Thus, we characterized the exochorium of the eggs of several triatomine hybrids and compared them with the parents, to assess the pattern of segregation and test the hypothesis of maternal inheritance. Hybrids were obtained in at least one direction from all crosses. The analysis of the exochorium of the eggs of the hybrids showed different patterns of segregation: exclusively paternal, predominantly maternal, predominantly paternal, mutual, and differential. Curiously, none of the hybrids evaluated presented characteristics that segregated exclusively from the female parental species. Thus, we demonstrate that the hypothesis of maternal inheritance of the exochorium pattern of eggs is not valid and we emphasize the importance of alternative/combined tools (such as integrative taxonomy) for the correct identification of these insect vectors (mainly in view of possible natural hybridization events due to climate and environmental changes).